2014
DOI: 10.1177/0883073814550188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nerve Conduction Studies in Obese Children With Insulin Resistance or Impaired Glucose Tolerance

Abstract: The aim of the study was to investigate nerve conduction studies in terms of neuropathic characteristics in obese patients who were in prediabetes stage and also to determine the abnormal findings. The study included 69 obese adolescent patients between April 2009 and December 2010. All patients and control group underwent motor (median, ulnar, tibial, and peroneal) and sensory (median, ulnar, sural, and medial plantar) nerve conduction studies and sympathetic skin response test. Sensory response amplitude of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
7
0
1
Order By: Relevance
“…An attenuate cerebrovascular reserve (CVR) has been observed in patients with diabetes or non-diabetic IR (39,40). Previous studies discovered that IR is involved in CVR through Bayliss effect, and chemical, neuronal, and metabolic mechanisms (41)(42)(43)(44). Last, IR enlarges the role of modifiable risk factors in IS, such as hypertension, diabetes, dyslipidemia, and cigarette smoking (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…An attenuate cerebrovascular reserve (CVR) has been observed in patients with diabetes or non-diabetic IR (39,40). Previous studies discovered that IR is involved in CVR through Bayliss effect, and chemical, neuronal, and metabolic mechanisms (41)(42)(43)(44). Last, IR enlarges the role of modifiable risk factors in IS, such as hypertension, diabetes, dyslipidemia, and cigarette smoking (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic neuropathy is common in diabetes populations with potential dysfunctions of cardiovascular, gastrointestinal, genitourinary systems and sudomotor or ocular functions [4,5]. In addition, recent studies have shown that individuals with oral glucose intolerance can also develop autonomic neuropathy [6][7][8]. Sudomotor function disturbance is considered one of the initial components of autonomic neuropathy, and its assessment may contribute to the detection of autonomic dysfunction in diabetics; in fact, the American Diabetes Association suggests that sudomotor function assessing small fiber status should be included in the diagnostic tests for the detection of neuropathies in diabetes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nöronal gelişim, migrasyon, farklılaşma, miyelin üretimi gibi sinir sistemi ile ilişkili birçok önemli fonksiyonda görev alır (4)(5)(6). Hiperglisemi ve obeziteye ait diğer komplikasyonlar da sinir hasarına neden olabilmektedir (7,8). Bu sebeplerle artan çocukluk çağı obezitesi prevalansı sinir sistemine ait komplikasyonların erken yaşlarda başlamasına neden olabilmektedir.…”
Section: Introductionunclassified